The Effectiveness of Electronic Services for Land and Building Tax-Rural and Urban in Tuban Regency - Yulisrowati, Iis; Tukiman, Tukiman (Universitas Muhammadiyah Ponorogo, 2024)
Taxes are one of the main revenues for the Indonesian State. Land and Building Tax-Rural and Urban (PBB P2) is a state tax imposed on land and buildings of a material nature, which the amount of tax payable is determined by the condition of the object, including land, funds or buildings. In improving the quality of services, Tuban Regency has implemented E-Government innovations in accordance with Tuban Regent Regulation Number 1 of 2019 concerning the implementation of non-cash transactions within the Tuban Regency Government, thus Tuban Regency has made an innovation called as Electronic Land and Building Tax-Rural and Urban (E-PBB P2) through the BPPKAD which aims to provide convenience for the public to find out information related to the E-PBB P2 and to be able to make payments independently through the Collecting Agents provided. The purpose of this research is to determine the effectiveness of Electronic services for Land and Building Tax-Rural and Urban implemented at the Regional Revenue, Financial and Asset Management Agency (BPPKAD) in Tuban Regency. The method used in this research was descriptive-qualitative method using data collection techniques in the form of interviews, observation and documentation, as well as applying Budiani's theory with 4 indicators, including (1) Program Targets (2) Program Socialization (3) Program Objectives, and (4) Program Monitoring. The research results show that the E-PBB P2 service in Tuban Regency has been running effectively but is still not optimal.